The Influence of Teamwork and Leadership Style towards Employee Productivity in Retail Store - Jasmine, Sephia; Hongdiyanto, Charly (Jurnal Entrepreneur dan Entrepreneurship, 2023)
Employees are one of the most critical assets considered the driving force of operations in a company. Many companies can determine their success by paying attention to employee productivity. In the retail store, the employee’s productivity relates to how employees can carry out daily operational to-do list targets, punctuality, and initiative. Several factors, such as Leadership, teamwork, and environment, can influence employees' productivity in a company. The support of the organization is critical in creating a comfortable environment for the employees to work. Trust can be given through Leadership and a comfortable co-team. With the proper support from the externals, the employee can perform better on the work. This research was conducted to analyze the effect of teamwork and leadership style on employee productivity with Trust as a mediator. This research was conducted quantitatively, and the data will be analyzed using PLS. The subject includes employees of a store. The sampling technique used is saturated sampling. The results of this study indicate that Trust mediates the effect of leadership style on employee productivity. In addition to the mediation test, it can be concluded that Trust mediates the effect of teamwork on employee productivity.